Social commerce’s effects on youth purchase intention: a case study in Mukah Sarawak - Ezuddin, Nur Anisah; Shukri, J.M. (Universiti Teknologi MARA, Sabah, 2025)
This study examines the effects of trust, perceived ease of use, perceived usefulness, and social commerce constructs on consumer purchase intention among Generation Z in Mukah, Sarawak. As internet usage and social media engagement rise, particularly among rural youth, social commerce has emerged as a significant trend. However, concerns over fraud and negative online experiences remain. Using a quantitative approach and data collected from 386 respondents, the study reveals that all four factors have a significant positive influence on purchase intention. Among them, perceived usefulness has the strongest impact, followed by social commerce constructs, trust, and perceived ease of use. These findings underscore the importance of enhancing platform usability, building trust, and leveraging social features to boost engagement in rural social commerce. The study provides valuable insights for online businesses and policymakers aiming to strengthen digital participation in underserved communities.